Kondisi Politik Persia pada Era Dinasti Qajar 1796-1834 M - Pramasto, Arafah (Rihlah: Jurnal Sejarah dan Kebudayaan, 2019)
AbstractThe Qajar dynasty in Indonesian literature is not as popular as the Safavid dynasty and the 1979 Iranian revolution. The role of Qajar dynasty started as one of the tribal powers among the Qizilbash elite troops of the Safavid dynasty. Political conditions during the decline of Safavids led to the emergence of other warring dynasties to gain domination in Persia. Qajar dynasty under the leadership of Agha Muhammad Khan was successful in defeating warring dynasties as the Russian invaders were also driven out. Agha Muhammad later became the Shah of Persia in 1796 year before he was assassinated during a military campaign against Russia. After his assassination, Fath Ali – nephew of Agha Muhammad became the new Shah in 1798. Qajar dynasty under the new reign effectively consolidated the political condition and governing aspect of Persia. Fath Ali is also believed to have committed violence against his competitors while also; he was able to coordinate between various cultural identities in Persia along with building country’s governing structure as well as patronizing religious life. During later wars with Russia, Fath Ali was dependent on intervention of British and French due to lack of reforms in his military. It became an important event before his death in 1834.